Social Networks Mining and Analysis of Specific Groups (Political and Regional) by using API - Farhan Khan; Saqib Saqib; Pireh Soomro; Asif Laghari; Kamran Memon (EAI Endorsed Transactions on Scalable Information Systems, 2020)
People have informal conversations on social media sites (Twitter, Facebook, etc) that shed light on the current issuesaround the world – opinions, and concerns about the learning process. Data from such environments can provide valuableinformation to predict the future to make effective decision making, however, the usage of such data is challenging. Thecomplexity of such data from social media content requires the use of human understanding as well as social networkanalysis to make predictions. We focused on political groups around the world to discover linkages behind the Terrorismaround the World to make predictions depend upon the data available. In this research paper, we focused on tweets relatedto the politicians and communities based on hashtags like #Syria #Weapons #Terrorist, etc. to identify the linkages of theuser who are talking about these issues depending upon the HashTag we used for the content analysis of social network byusing Gephi to make a prediction.